LEARNING WITH A SMILE: GAMES AND EXPERIENCES IN ORGANIC CHEMISTRY - Yusufova, Sabina; Valieva, Elvina (SAMBHRAM XABARNOMASI, 2024)
Annotation: The pedagogical process is a set of lessons, extracurricular educational work, carried out by the teaching and student staff according to one plan. The training mainly uses seminar lessons, practical and laboratory work, in which various methods and means are used. The increase in mental load in the classroom makes us think about how to maintain students’ interest in the material being studied and their activity throughout the lesson. We have to look for effective teaching methods and methodological techniques that would activate the thoughts of schoolchildren and stimulate them to independently acquire knowledge. We must ensure that the student works actively and enthusiastically during lessons, and use this as a starting point for the emergence and development of curiosity and deep cognitive interest. The purpose of the article is to identify factors and pedagogical conditions for the successful use of games aimed at enhancing the cognitive activity of schoolchildren when studying organic chemistry. Аннотация. Педагогический процесс представляет собой совокупность уроков, внеклассной воспитательной работы, проводимых профессорско-преподавательским и студенческим коллективом по единому плану. В обучении преимущественно используются семинарские занятия, практические и лабораторные работы, в которых используются различные методы и средства. Увеличение умственной нагрузки на уроке заставляет задуматься о том, как сохранить интерес учащихся к изучаемому материалу и их активность на протяжении всего урока. Приходится искать эффективные методы обучения и методические приемы, которые бы активизировали мышление студентов и стимулировали их к самостоятельному приобретению знаний. Мы должны обеспечить, чтобы студент активно и увлеченно работал на уроках, и использовать это как отправную точку для возникновения и развития любознательности и глубокого познавательного интереса. Цель статьи - выявить факторы и педагогические условия успешного использования игр, направленных на активизацию познавательной деятельности студентов при изучении органической химии.